Bile salts enhance the susceptibility of the peach allergenic lipid transfer protein, Pru p 3, to in vitro gastrointestinal proteolysis - Kai Wang; Judit Gali-Moya; Maria Ruano-Zaragoza; Kathleen Cain; Giovanni D’Auria; Matthew Daly; Perdita Barran; René Crevel; E. N. Clare Mills (Scientific Reports, 2023)
Abstract Sensitisation to the lipid transfer protein Pru p 3 is associated with severe allergic reactions to peach, the proteins stability being thought to play a role in its allergenicity. Lipid binding increases susceptibility of Pru p 3 to digestion and so the impact of bile salts on the in vitro gastrointestinal digestibility of Pru p 3 was investigated and digestion products mapped by SDS-PAGE and mass spectrometry. Bile salts enhanced the digestibility of Pru p 3 resulting in an ensemble of around 100 peptides spanning the protein’s sequence which were linked by disulphide bonds into structures of ~ 5–6 kDa. IgE binding studies with a serum panel from peach allergic subjects showed digestion reduced, but did not abolish, the IgE reactivity of Pru p 3. These data show the importance of including bile salts in vitro digestion systems and emphasise the need to profile of digestion in a manner that allows identification of immunologically relevant disulphide-linked peptide aggregates.